Recovering Biblical manhood and womanhood a response to evangelical feminism - Piper, John, 1946-; Grudem, Wayne A., 1948- (Wheaton, IL Crossway, 1991)
Includes bibliographical references and indexes.
Keywords: Men (Christian theology) -- biblical teaching; Woman (Christian theology) -- biblical teaching; Sexuality -- biblical teaching